Campylobacter jejuni em frangos de corte, carne e vísceras de frango no Rio Grande do Sul e efeito do congelamento sobre a contaminação nos cortes - Boufleur, Róger (2009)
Campylobacteriosis, in the current days, is recognized as the major cause of foodborne illness in many developed and developing countries. Among the Campylobacter species responsable for the infections, C. jejuni is responsable for 75% of the cases of human campilobacteriosis, as for it, it s considered as the major species involved on the registered cases. In this work, two experiments were conduced. In the first, the presence of C. jejuni and Campylobacter spp. in poultry farms of Rio Grande do Sul State in Brazil was investigated. Epidemiological data was obtained with the person encharged by the farms, and the data obtained was corelated with the levels of contamination of each property. In the second experiment, we investigated the contamination of cicken meat and giblets adquired in supermarkets in Santa Maria city of C. jejuni as well as the freezing effect on the contamination levels in this samples. For the first trial, 280 cloacal swabs were collected from four poultry farms. In the second experiment, 9 samples of heart, liver, gizzard and drumette, tottalizing 36 samples collected. A portion of each sample was processed freshly, while the rest was freezed (-18ºC) for 7 days before it s processing. In the first trial, 147 samples (52,5%) were positive for C. jejuni and another 31 (11,07%) were identified as Campylobacter spp. The data analysis revealed correlaction beetwen the number of birds kept in de farms (p=0,05), the age of the poultry (p=0,05) and the gender (p=0,03), as female was more infected than males. In the second experiment, isolation of C. jejuni was achieved in 7 heart (77,7%), 8 liver (88,8%), 4 gizzard (44,4%) and 3 drumette (33,3%) fresh samples, corresponding to 61,1% of total samples. After freezing storage, in only 3 samples (two liver and one heart) C. jejuni was isolated (8,3%). The data obtained allowed us to conclude that C. jejuni is widely spread in poultry farms os Rio Grande do Sul state, so, improve the control procedures for Compylobacter species on the poultry fars is needed. The chicken cuts obtained from supermarkets in Santa Maria city are also higly contaminated by C. jejuni, however, freezing storage for seven days can drastically reduce the contamination levels of chicken cuts, improoving food safety, althoght, this procedure do not eliminate completely C. jejuni from de cuts analized, and the correct manipullation is needed to eliminate the risk of infeccion from poultry meat sources .